Facile Synthesis of Germanium Nanocrystals and Their Application in Organic-Inorganic Hybrid Photodetectors - Xue, Ding-Jiang; Wang, Jian-Jun; Wang, Yong-Qing; Xin, Sen; Guo, Yu-Guo; Wan, Li-Jun (Advanced materials (Weinheim), 2011)
A solution‐based method is developed for the synthesis of colloidal Ge nanocrystals (NCs), which directly grow from germanium(II) bromide in an oleylamine solution with no extra reducing agents. Hybrid photodetectors based on the NCs and poly(3‐hexylthiophene) (P3HT) show promise for large‐area applications, as revealed by their high photoresponse ratio, high sensitivity, and high stability.